2017
DOI: 10.1158/0008-5472.can-16-0655
|View full text |Cite
|
Sign up to set email alerts
|

The NCI-60 Methylome and Its Integration into CellMiner

Abstract: A unique resource for systems pharmacology and genomic studies is the NCI-60 cancer cell line panel, which provides data for the largest publicly available library of compounds with cytotoxic activity (~21,000 compounds), including 108 FDA-approved and 70 clinical trial drugs as well as genomic data, including whole-exome sequencing, gene and microRNA transcripts, DNA copy number, and protein levels. Here we provide the first readily usable genome-wide DNA methylation database for the NCI-60, including 485,577… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 36 publications
(76 reference statements)
3
67
0
Order By: Relevance
“…Data source comparisons. CellMinerCDB integrates four prominent cancer cell line data sources (CellMiner NCI-60 (2,(8)(9)(10), Sanger/Massachusetts General Hospital GDSC (3), the Broad/Novartis CCLE, and the Broad CTRP) (5,6) and a tissue-specific dataset encompassing 66 small cell lung cancer lines (NCI SCLC) (11) (Figure 1). Collectively, these sources provide drug activity and molecular profiling data for approximately 1,400 distinct cancer cell lines (Figure 1b, Supplementary Data).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Data source comparisons. CellMinerCDB integrates four prominent cancer cell line data sources (CellMiner NCI-60 (2,(8)(9)(10), Sanger/Massachusetts General Hospital GDSC (3), the Broad/Novartis CCLE, and the Broad CTRP) (5,6) and a tissue-specific dataset encompassing 66 small cell lung cancer lines (NCI SCLC) (11) (Figure 1). Collectively, these sources provide drug activity and molecular profiling data for approximately 1,400 distinct cancer cell lines (Figure 1b, Supplementary Data).…”
Section: Resultsmentioning
confidence: 99%
“…Despite ongoing data acquisition and processing efforts, gaps exist with respect to genomic profiling data in sources other than the CellMiner NCI-60 ( Figure 1b, dark grey table entries). For the GDSC gene mutation and methylation data, we took advantage of processing pipelines developed for the NCI-60 (10,12) to compute gene-level summary data from publicly available raw data. Remaining source-specific molecular profiling data gaps can be filled within CellMinerCDB by effectively extending data provided by one source to another.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a previously reported analysis of DNA methylation using the cancer cell line panel NCI60 has identified SLFN11 CpG promoter island hypermethylation as a predictive biomarker of platinum resistance (18,26). Some studies have revealed that the DNA methyltransferase (22).…”
Section: Discussionmentioning
confidence: 99%